Wacana Tandingan Puritanisme Islam Tentang Peran Perempuan (Mengkaji Bangunan Epistemologi Hukum Taqi Al Din Al Nabhani - Isnatin Ulfah (Justicia Islamica, 2014)
Religious puritanism was born as a counter-discourse, especially against modernity. Social factors are always taken into consideration to understand the presence of puritanism. However, it cannot be denied that it is also strongly influenced by the encouragement contained in the religious teachings themselves (inward oriented). Its rejection of the West and its cultural products, for example gender equality, can be seen from this side, namely its literalist and textualist character. It is from this side that this paper is written, to find out the epistemological perspective of puritan groups in understanding religious texts on the role of women.